The Influence of Islamicity Performance Index and Non Performing Financing on Return on Asset of Indonesian Sharia Commercial Bank - Seppi Mustion; Ahmad Wira; Aidil Novia (Universitas Muhammadiyah Surabaya, 2023)
This research aims to analyze the ability of the Islamicity Performance Index to mediate NPF on profitability in Islamic banks in Indonesia for the 2017-2021 period. This research uses a type of research using a quantitative approach. The population of this research is all sharia commercial banks in Indonesia with a sample size of 9 banks. Sampling was carried out using a purposive sampling method. Data collection uses secondary data, namely documentation techniques by taking the annual reports of each Islamic commercial bank in Indonesia. The data analysis technique uses multiple linear regression analysis. The results of this research show that non-performing financing has a negative influence on ROA and the profit sharing ratio has a positive influence on Return on Assets and the Islamic Income Ratio has a positive influence on Return on Assets and the Islamic Investment Ratio has a positive influence on Return on Assets. Furthermore. Keywords: Islamicity Performance Index, NPF, ROA Penelitian ini bertujuan untuk menganalisis Kesanggupan Islamicity Performance Index memediasi NPF Terhadap ROA pada bank syariah di Indonesia periode 2017-2021. Penelitian ini menggunakan jenis penelitian memakai pendekatan kuantitatif. Populasi penelitian ini adalah semua bank umum syariah di Indonesia dengan jumlah sampel sebanyak 9 bank. Penarikan sampel dilakukan dengan metode purposive sampling. Pengumpulan data menggunakan data sekunder yaitu dengan teknik dokumentasi dengan mengambil pada annual report masing-masing bank umum syariah di Indonesia. Teknik analisis data menggunakan analisis regresi linier berganda. Hasil dari penelitian ini menunjukkan bahwa non performing financing terhadap ROA Berpengaruh negatif dan profit sharing ratio Berpengaruh Positif Terhadap Return On Asset dan Islamic Income Ratio Berpengaruh Positif Terhadap Return On Asset serta Islamic Investment Ratio Berpengaruh Positif Terhadap Return On Asset selanjutnya Kata Kunci :Islamicity Performance Index, NPF , ROA